An investigation into the association between diet and dementia risk. (31st December 2021) - Dobreva, Ivelina; Mukadam, Naaheed; Solmi, Francesca
Abstract: Background: The number of people living with dementia is rising. It is estimated that by 2030, the total number of people with dementia would reach 82 million. By 2050, the number would increase to 152 million. Modifiable risk factors are gaining increasing attention as means of prevention or delaying of the disease. A number of those factors relate to diet, however specific patient guidance has not been established due to inconsistent evidence, heterogeneity of samples, small effect and sample sizes. We aimed to use a large sample with long follow up times to clarify links between dietary factors and dementia. We use data from the UK Biobank cohort [enrolment from years 2006‐ 2010] on dietary patterns and registered dementia cases to establish an association between diet and dementia risk.We investigate the association between adherence to the Mediterranean diet, as well as specific aspects such as vegetarianism and high versus low fat which could have an impact on dementia risk.This will help in establishing specific guidance for reduction in dementia risk. Method: We will combine variables to form quantiles of low, medium and high adherence to the Mediterranean diet. We will also classify people into those adhering to a vegetarian/non‐vegetarian diet and those eating a low versus high fat diet. We will summarise characteristics of the sample and compare those developing and not developing dementia. Dementia diagnosis will be determined from self‐report and recorded diagnoses in electronic health records. We will conduct a Cox regression to investigate the effect of dietary factors on dementia risk, adjusting forage, sex, education, physical activity and cardiovascular risk factors. Result: Results will be presented in the form of summary tables as well as results of Cox regression models. We will examine which dietary factors have the biggest impact on dementia risk and, if supported by the evidence, we will provide suggestions as to how to reduce dementia risk through dietary adjustments. Conclusion: This project examines association between diet and dementia risk.